Tumor de células da granulosa associado a leiomioma em ovário equino: relato de caso - Paz, Letícia Bisso (2024)
Ovarian dysfunction in mares can arise from several conditions, but ovarian neoplasms are the least frequent cause. Nevertheless, different types of ovarian tumors have been described in this species, with granulosa cell tumor (GCT) being the most prevalent. Definitive diagnosis is achieved only through histopathological examination, consequently, the treatment of choice for this condition involves surgical removal of the affected ovary through ovariectomy. The objective of the present study is to describe the case of a five-year-old Quarter Horse mare, which was treated at the Animal Reproduction Sector of FMVZ UNESP – Botucatu presenting reproductive failure. After a complete anamnesis, physical examination, gynecological examination and complementary tests, the suspicion of an ovarian tumor was raised. Therefore, the patient underwent left unilateral ovariectomy to remove the affected ovary and was diagnosed through histopathological examination with a granulosa cell tumor associated with leiomyoma. Ovarian leiomyoma is an uncommon finding, and the simultaneous presence of two tumor types in the same tissue is rare in equine species, emphasizing the importance of seeking a definitive diagnosis in cases of ovarian tumors in mares.